Legal Protection of Heirs in the Disbursement of Inheritance Assets (A Case Study of District Court Decision Number 218/Pdt.G/2021/PN.Dps) - Tumbel, Cindy Valencya; Priadharsana, I Made (JURNAL AKTA, 2024)
Inheritance is said to occur when someone has died. Arrangements for the distribution of property belonging to someone who has died to his heirs in Indonesia are regulated in inheritance law. The regulation of inheritance law in Indonesia is regulated according to Islamic Law and the Civil Code. For a person who adheres to Islam, he follows the provisions of Islamic inheritance law and other than that, he follows the provisions of the Civil Code. The problem of inheritance disputes is something that has occurred in the community due to the problem of fighting over who is the heir, unfair inheritance shares, or disbursement of testamentary property that takes a long time. In this paper, the author will discuss an inheritance case where the bank as the depository of the inheritance from the testator does not want to give it to the heirs. It is hoped that this writing will provide new knowledge to readers regarding the inheritance disbursement procedure in Indonesia.